Exploring the mechanism of aloe-emodin in the treatment of liver cancer through network pharmacology and cell experiments - Zhu, Mingyang; He, Qingmin; Wang, Yanan; Duan, Liying; Rong, Kang; Wu, Yingying; Ding, Ye; Mi, Yang; Ge, Xiaoyang; Yang, Xiaocui; Yu, Yong (Frontiers in Pharmacology, 2023)
Objective: Aloe-emodin is an anthraquinone compound extracted from the rhizome of the natural plant rhubarb. Initially, it was shown that AE exerts an anti-inflammatory effect.Further studies revealed its antitumor activity against various types of cancer. However, the mechanisms underlying these properties remain unclear. Based on network pharmacology and molecular docking, this study investigated the molecular mechanism of AE in the treatment of hepatocellular carcinoma, and evaluated its through in vitro experiments.Methods: Databases was used to identify potential drug and disease -related targets.Intersection genes were obtained through the Venn diagram.GO and KEGG enrichment analyses of intersecting genes were conducted by Bioinformatics.Intersection genes were introduced into STRING to construct a protein-protein interaction network,Cytoscape3.9.1 software was used to visualize and analyze the core targets. AutoDock was utilized to achieve molecular docking between drug and core targets. In vitro experiments investigated the therapeutic effects and related mechanisms of AE.Results: 63 overlapped genes were obtained and GO analysis generated 3,646 entries by these 63 intersecting genes. KEGG analysis mainly involved apoptosis, proteoglycans in cancer, TNF signaling pathway, TP53 signaling pathway, PI3K-AKT signaling pathway, etc. AKT1, EGFR, ESR1, TP53, and SRC have been identified as core targets because the binding energies of them between aloe-emodin were less than -5kcal/Mol.The mRNA and protein expression, prognosis, mutation status, and immune infiltration related to core targets were further revealed. The involvement of AKT1 and EGFR, as well as the key target of the PI3K-AKT signaling pathway, indicated the importance of this signaling pathway in the treatment of HCC using AE. The results of the Cell Counting Kit-8 assay and flow analysis demonstrated the therapeutic effect of AE. The downregulation of EGFR, PI3KR1, AKT1, and BCL2 in mRNA expression and PI3KR1, AKT,p-AKT in protein expression confirmed our hypothesis.our study initially showed that AE exerted a therapeutic effect on HCC by modulating multiple signaling pathways. Various analyses confirmed the antiproliferative activity and pro-apoptotic effect of AE on HCC through the PI3K-AKT signaling pathway. This study revealed the therapeutic mechanism of AE in the treatment of HCC through a novel approach, providing a theoretical basis for the clinical application of AE.